2011
DOI: 10.5539/ijms.v3n4p63
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Source Credibility on Saudi Consumer’s Attitude toward Print Advertisement: The Moderating Role of Brand Familiarity

Abstract: An endorser or a spokesperson is frequently used by marketers in their product advertisements as a credible source that is hoped to influence the attitude of consumers in the marketplace toward the shown advertisement, the brand and most importantly their purchase intentions. Corporate credibility C/C -the reputation of a company for honesty and expertise is another type of source credibility that is said to influence consumers' reaction to the shown product advertisements and shape their attitudes to brands. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 34 publications
(65 reference statements)
3
28
0
Order By: Relevance
“…Similarly, multiple regression analysis showed that perceived credibility had a significant association with App, consistent with previous studies (Sallam, 2011;Doss, 2011). Credible sources lead to formation of positive consumer attitudes (Yogci et al, 2009).…”
Section: Discussion Limitation and Conclusionsupporting
confidence: 90%
“…Similarly, multiple regression analysis showed that perceived credibility had a significant association with App, consistent with previous studies (Sallam, 2011;Doss, 2011). Credible sources lead to formation of positive consumer attitudes (Yogci et al, 2009).…”
Section: Discussion Limitation and Conclusionsupporting
confidence: 90%
“…This entails the hypothesis that:-H3b: Attitude toward advertisement mediates celebrity's expertise and consumer's purchase intention of footwear in Malaysia Findings by Comiati & Plăias (2010) suggested significant relationship between attractiveness consumer's reactions toward advertisement, based upon different circumstances that the celebrity endorsement approach is applied. Sallam (2011) further proposed the indirect relationship between the dimensions of celebrity credibility on purchase intention, through attitude toward advertisement and attitude toward brand. Therefore, this study accounts for attitude through advertising between celebrity's attractiveness and purchase intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings of this study are consistent with previous studies indicating the positive relationship between credibility and consumers' attitude (Abdul Azeem & Zia ul Haq, 2012). If consumers have favorable perception toward the organizations, they will be likely to have a positive attitude toward advertising because they will perceive the organizations' products and services positively (Sallam, 2011). Based on the discussion above, credibility is a very significant determinant to consumers and provides values for them.…”
Section: Discussionmentioning
confidence: 99%
“…(Goldsmith et al, 2000). If consumers have favorable perception toward the organizations, they will be likely to have positive attitude toward advertising because they will perceive the organizations' products and services positively (Sallam, 2011). Petty and Cacioppo (1986) stated that trustworthiness element in the advertisements' contents can increase the consumers' response rate toward advertising.…”
Section: Credibilitymentioning
confidence: 99%